Molecular docking of piperine, limonene, and eugenol in black pepper (Piper nigrum L.) as anti-stroke - Azzahra, Fauzia; Nadapdap, Ezra Gabriella Oktaviany; Cahyani, Nabila; Salsabila, Fathul Aini; Afada, M. Mufti; Auli, Winni Nur; Saputro, Anjar Hermadi (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2024)
Stroke remains a leading cause of death and disability worldwide, necessitating the development of effective therapeutic agents. This study explores the potential of bioactive compounds from Piper nigrum L. (black pepper) as anti-stroke candidates targeting the cGMP-specific phosphodiesterase 5A (PDE5A) receptor (PDB ID: 3BJC). The evaluation employed molecular docking and drug-likeness assessment methodologies. Piperine, limonene, and eugenol were assessed using Lipinski's Rule of Five (RO5) to predict oral bioavailability. All compounds met the RO5 criteria, indicating favorable drug-likeness characteristics. Molecular docking was validated through re-docking of the native ligand WAN, yielding an RMSD ≤ 2 Å, confirming the accuracy of the docking protocol. Following validation, molecular docking analysis revealed that piperine demonstrated the lowest binding energy (-7.71 kcal/mol), followed by limonene (-5.28 kcal/mol) and eugenol (-4.86 kcal/mol). Visualization results revealed that piperine shared key interaction motifs and amino acid residues with the native ligand, including hydrogen bonding and hydrophobic interactions, indicating strong receptor affinity and molecular stability. Additionally, the ligand-receptor interaction distance of piperine (2.21 Å) closely resembled the native ligand (2.15 Å), further supporting its structural and functional similarity. These findings highlighted piperine as the most promising anti-stroke candidate among the tested compounds. Further in vitro and in vivo studies are recommended to validate its pharmacological efficacy and safety.